Export growth and domestic performance - Pereira, A. M.; Xu, Z. (Review of International Economics, 2000)
A VAR approach is used to analyze the effects of export growth on the evolution of GDP, domestic employment, and investment in 39 economies. The results strongly support the export-led growth hypothesis. Export growth effects GDP growth positively in 30 countries. In six countries, all of them inward-looking, the effects are negative. For these countries, and for these countries alone, export growth has a negative effect on the evolution of both domestic employment and investment. This also suggests the importance of the indirect effects of exports on GDP growth.